Changes in nutrient content of rye, triticale, and wheat whole-plant forages with maturity - Hanson, K.L.; Schalles, R.S.; Harbers, L.H.; Thompson, Curtis R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We compared upland and bottomland cereals seeded during 1991 at the KSU Agricultural Research Center - Hays. The five crops (three varieties of triticale, a winter wheat, and a winter rye) were harvested as whole plants during the latter part of the growing season. Crude protein (CP), ac id detergent fiber (ADF), and neutral detergent fiber (NDF) were estimated using near infrared spectroscopy. Compute r models were developed to describe nutrient changes. Crude protein content decreased whereas the two fiber components increased with maturity. Rye and wheat tended to have lower CP values when day 125 was used as the arbitrary harvest date. We observed only slight differences i n nutritional components between upland and bottomland plantings.
Keywords: Beef; Nutrient content; Triticale; Wheat; Rye; Hay